2011
DOI: 10.1097/jto.0b013e31821038ab
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Radiological Study of Thin-Section Computed Tomography to Predict Pathological Noninvasiveness in Peripheral Clinical IA Lung Cancer (Japan Clinical Oncology Group 0201)

Abstract: Although our predetermined criterion for specificity was not statistically confirmed, radiological diagnosis of noninvasive lung cancer with a thin-section computed tomography scan corresponded well with pathological invasiveness. Radiological noninvasive peripheral lung adenocarcinoma could be defined as an adenocarcinoma ≤2.0 cm with ≤0.25 consolidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
397
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(433 citation statements)
references
References 20 publications
15
397
2
1
Order By: Relevance
“…We believe that these radiological evaluations can be subjective and can affect the outcomes of such studies directly. Our main concern is that radiological evaluations may result in discrepancies in outcomes among studies, including those of this study (1)(2)(3)5 (8). Therefore, the median follow-up time used by Hattori et al was too short to confirm their conclusion regarding the importance of the GGO component as a significant clinical T descriptor.…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…We believe that these radiological evaluations can be subjective and can affect the outcomes of such studies directly. Our main concern is that radiological evaluations may result in discrepancies in outcomes among studies, including those of this study (1)(2)(3)5 (8). Therefore, the median follow-up time used by Hattori et al was too short to confirm their conclusion regarding the importance of the GGO component as a significant clinical T descriptor.…”
mentioning
confidence: 38%
“…Based on the pathoradiological correlation results in the Japan Clinical Oncology Group (JCOG) 0201 study (2,3), the radiological criterion to distinguish noninvasive from invasive lung adenocarcinoma is defined as a CTR ≤0.50 in c-T1a and c-T1b tumors (<3 cm), and an excellent prognosis is predicted for such radiologically defined noninvasive adenocarcinomas (2,3). However, in their study, Hattori et al evaluated and compared OS between patients with GGO-dominant (0< CTR ≤0.50) and solid-dominant tumors (0.5< CTR <1.0) in patients with radiologically partsolid lung cancer (these cases were all adenocarcinomas).…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14] Accordingly, clinical trials of reductive surgery for various small lung cancers have been performed. Several studies have indicated that limited resection is an appropriate surgical procedure for non-solid nodules observed on HRCT and the majority of these nodules were pathologically shown to be adenocarcinoma in situ.…”
Section: Discussionmentioning
confidence: 99%
“…In pT1abN0M0 lung cancers, tumour size is not the only measure of malignancy, as tumour shadow disappearance rate (TDR), 2) visual estimation of the consolidation component, 2,3) solid component size, 4) maximum standardised uptake values (SUVmax) from 18F-fluorodeoxyglucose positron emission tomography (PET)/CT, 5) ratio of the size of solid attenuation to the maximum tumour dimensions (consolidation/tumour [C/T] ratio), 6,7) lymphatic invasion, 8) proportion of ground-glass opacity (GGO) 9) and tumour necrosis 10) have also been reported as prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up lasted for at least 5 years. Based on thin-section CT scan, patients were divided according to the consolidation to maximum diameter ratio (C/T) (13). In the group of patients with C/T ≤0.5, which included 46 segmentectomies and 1 lobectomy, all patients were diagnosed with adenocarcinoma.…”
Section: Editorialmentioning
confidence: 99%